The Effect of Surgical Technic Selection on Posttonsillectomy Bleeding Probability - Kapusuz, Zeliha; Sakallıoğlu, Öner; Göçmen, Yeşim; Saydam, Levent (Fırat University, 2012)
Objective: To compare the post tonsillectomy bleeding rates which need to control under general anesthesia after tonsillectomies performed by using bipolar cautery and blunt dissection technic. Materials and Method: The charts of 397 patients who undergone tonsillectomy between January 2008 and February 2010 were evaluated retrospectively and the patients with post tonsillectomy bleeding which need to control under general anesthesia were determined. Post tonsillectomy bleeding rates which need to control general anesthesia in groups that performed two different tonsillectomy technics were compared with chi-square test. Results: 222 (55.9 %) man and 175 (44.1 %) women patients were included to the study, 59 (14.8%) were over and 338 (85.2 %) were under 16 years old. While 188 (47.3 %) patients were operated by bipolar cautery tonsillectomy, 209 (52.7%) patients were operated by blunt dissection tonsillectomy. In 1 patient, (0.5 %) who underwent tonsillectomy by bipolar cautery was need to control for post tonsillectomy bleeding under general anesthesia. In 7 patients, (3.3%) who underwent tonsillectomy by blunt dissection was need to control for post tonsillectomy bleeding under general anesthesia. While the post tonsillectomy bleeding happened on postoperative first day in 4 of 8 patients (50%), in the other 4 of 8 patients (50 %), post tonsillectomy bleeding happened on postoperative between 7-14 days who need to control of bleeding. All of patients who need to control of bleeding under general anesthesia were under 16 years old. Conclusion: We found no statistically significant difference for post tonsillectomy bleeding probability between bipolar cautery tonsillectomy

Amaç: Tonsillektomi hastalarında bipolar koter ve klasik künt diseksiyon kullanımı sonrası, genel anestezi altında kontrolü gereken kanama oranlarını araştırmak. Gereç ve Yöntem: Ocak 2008 ve şubat 2010 tarihleri arasında tonsillektomi yapılan 397 hasta retrospektif olarak değerlendirildi. Operasyon sonrasında genel anestezi altında müdahale gerektiren kanamalı olgular tespit edildi. İki farklı yöntemle yapılan tonsillektomi sonrası genel anestezi altında kontrolü gereken kanama oranları karşılaştırıldı. İstatiksel değerlendirme Ki-kare testi kullanılarak yapıldı. Bulgular: Hastaların 222 (%55,9)'si erkek, 175 (%44,1)'i kadındı. Vakaların 59 (%14,8)'u 16 yaş üzerinde, 338 (85,2)'i 16 yaş altında idi. Yüzseksensekiz (%47,3) hastaya bipolar koter, 209 (%52,7) hastaya da künt diseksiyonla tonsillektomi yapıldı. Bipolar koterle tonsillektomi yapılan hastaların birinde (% 0,5) operasyon sonrası genel anestezi altında kanama kontrolüne gerek duyuldu. Klasik künt diseksiyonla tonsillektomi yapılan 7 (%3,3) hastada genel anestezi altında kanamaya müdahale yapıldı. Bu hastalardan dördünde (%50) postoperatif ilk gün de, diğer 4 (%50) hasta ise 7-14 günler arasında kanama ile karşılaşılmıştı. Genel anestezi altında müdahale edilen hastaların hepside 16 yaş altındaydı. İstatistiksel olarak bipolar koter ile künt diseksiyonla yapılan tonsillektomi sonrası genel anestezi altında kanamaya müdahale oranları arası anlamlı bir fark bulunamadı. Sonuç: Çalışmamızda tonsillektomi sonrası genel anestezi altında müdahale açısından klasik künt diseksiyonla bipolar koterle diseksiyon arasında bir fark izlenmemiştir.
Cerrahi Teknik Seçiminin Tonsillektomi Sonrası Kanama Olasılığı Üzerine Etkisi